1989
DOI: 10.1159/000205368
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic Syndrome Preceding Acute Myelomonocytic Leukemia with Dysplastic Marrow Eosinophilia and Inv(16)

Abstract: A 44-year-old Japanese male having refractory anemia with excess of blasts (RAEB) preceding acute myelomonocytic leukemia (AMMoL) with dysplastic marrow eosinophilia (M4Eo in the FAB classification) is reported. Sequential cytogenetic studies revealed a specific chromosomal abnormality, inv(16) (p13q22), when RAEB was first diagnosed and again when overt leukemic transformation compatible with M4Eo was manifested. However, during the interval between the RAEB and AMMoL, an unrelated abnormal karyotype without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Therefore, the diagnosis of MDS-Eo requires careful exclusion of other hematological disorders. To our knowledge, clonal eosinophilia with MDS has been previously reported in 5 cases [2, 3, 4, 5, 6]. In the case presented here, chromosomal aberration was identified in eosinophilic metaphase spreads by means of simple Giemsa staining, thus indicating that eosinophilia in our case was clonal proliferation.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Therefore, the diagnosis of MDS-Eo requires careful exclusion of other hematological disorders. To our knowledge, clonal eosinophilia with MDS has been previously reported in 5 cases [2, 3, 4, 5, 6]. In the case presented here, chromosomal aberration was identified in eosinophilic metaphase spreads by means of simple Giemsa staining, thus indicating that eosinophilia in our case was clonal proliferation.…”
Section: Introductionsupporting
confidence: 52%
“…To ascertain the clonality of the eosinophils, metaphase spreads overlaid with eosinophilic granules were analyzed as described previously (fig. 3b) [1, 2]. Briefly, by omitting trypsin treatment, we could observe eosinophilic cytoplasmic granules in some of the metaphase spreads, which were recognized as eosinophils.…”
Section: Case Reportmentioning
confidence: 99%
“…These abnormalities included t(5;12)(q33;p13), 20 inv16(p13q22), [17][18][19] and other abnormalities in chromosomes 7 or 16. 9,23,32,33 The t(5;12)(q33;p13) abnormality is less common but appears to be relevant for the pathogenesis of the eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, bone marrow eosinophilia or basophilia in MDS was observed in patients having complex karyotypes, 9,11 a chromosome 7 abnormality, 12 i(17q), 13 t(6;9), [14][15][16] inv16, [17][18][19] or t(5;12). 20 In our study, t(6;9) was observed in only 2 patients and neither inv16 nor t(5;12) was detected.…”
Section: Cytogeneticsmentioning
confidence: 99%
“…Alterations of the PEBP2␣B and PEBP2␤ genes have been associated with myelodysplasia (8,(40)(41)(42)(43). Neutrophils generated in vitro from PEBP2␤MYH11 transgenic bone marrow displayed unusual morphology.…”
Section: Discussionmentioning
confidence: 99%